Private Cloud Storage Using OpenStack with Simple Network Architecture - Albert Sagala; Ruth Marlina Hutabarat (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
The development of cloud computing was highly developed and increasingly in demand by many parties. Cloud computing was very helpful to user to perform data storage without preparing own physical device. Cloud storage is a part of cloud computing where it can facilitate user to upload and download files, view file status. The main barrier to implement the private cloud was the difficulty in configuration of many components involved. These conditions minimize the implementation of the private cloud in many parties. In this research, we demonstrate cloud storage architecture simply by using only three nodes with OpenStack. The first node is the controller, the second node is object storage and the third is object storage. Elaborating the component that should be activated to implement the private cloud. The result of this research will help parties who want to build private cloud storage with simple network architecture using OpenStack Object Storage.